Status of institutional repository of the Faculty of Medicine, University of Jaffna during the period from 2012 to 2021 - Ananthasothy, T.; Balakumaran, L.; Uthayakumar, L. (My University, 2022)
An institutional repository (IR)is an archive for collecting, preserving, and dissem inating digital copies of the intellectual output of an institution.IR of the Faculty of Medicine, the University of Jaffna, functions as a platform for faculty academics and researchers to host their research publications. This study analyzes the distri bution and extent of research publications available in the IR, and the pattern of articles published by the Faculties of Medicine and Allied Health Sciences at the University of Jaffna from 2012 to 2021. Further, the study identifies the names of the most prolific authors and their citations. A web search was conducted, and the data for the study were downloaded from the same IR. The research output of the Faculty of Medicine was collected from the Google Scholar profile using publish or perish version 8 database. The study revealed that IR categorized the seven communities and 62 sub-communities. A total of 1950 documents were uploaded under 24 types during the study period; among them, only 48.4% (n=944) of the documents were research publications, of which 15.88% (150) were journal full text. Department of Clinical Medicine (19.8%, n=187), Community & Family Medicine (18.1%, n=171) and Biochemistry (16.7%, n=158) have the highest num ber of research publications deposited in the IR. However, the total research output is 1187 during the study period (2012-2021) in Google Scholar. Considering the number of citations,Arasaratnam V is the top author with 959 citations for her 140 publications and 15 h index. The study suggested conducting frequent awareness programsfor faculty members and finding a mechanism to collect all publications to uplift faculty members’ promotions, university ranking, institutional visibility, and feasible foundation of institutional knowledge management and help to expose the grey literature.
Keywords: Digital repository; Faculty of Medicine; Institutional repository; University of Jaffna